Novelties of the Bromeliaceae family for the northwest of Michoacan, Mexico - García-Ruiz, Ignacio; Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 2014)
Hechtia purhepecha, a new species from Michoacán, Mexico is described and illustrated. The new taxon is compared with H. laxissima, a species with similar characteristics. Tillandsia guenther-nolleri Ehlers, a taxon known until now only from Colima and Jalisco, is recorded for the first time for the state of Michoacán.